Overview on Grant Writing for Graduate Student Research. Issue 9 (13th September 2022) - Smith, Diane; Chowdhury, Abu Sayeed; Oxford, Julia Thom
Abstract: Grant writing is an important skill to develop during graduate school. This article provides an overview of grant writing for graduate students. Specific topics covered include understanding your funding needs, identifying appropriate grant opportunities, analyzing the guidelines for the proposal, planning and time management, understanding the priorities of the funding agency or organization, proposal organization and writing strategies, additional forms and letters of support that may be required, the editing and revising process, and submission of your grant proposal. Courses and workshops are an efficient and effective way to be guided through the grant proposal writing process with a greater potential for positive outcomes. © 2022 Wiley Periodicals LLC.